Performance of low and medium-rise concrete frames under various intensities earthquake in Malaysia / Rozaina Ismail, Azlan Adnan and Azmi Ibrahim - Ismail, Rozaina; Adnan, Azlan; Ibrahim, Azmi (Universiti Teknologi MARA, Perlis, 2011)
This paper presents the vulnerability of public buildings in Malaysia subjected to earthquakes from Sumatra and Philippines. Tremors in Peninsular Malaysia and East Malaysia due to Sumatra and Philippine earthquakes have been reported several times. Engineers are concerned of the seismic vulnerability of public buildings due to lack of earthquake consideration in Malaysia's building design procedure. 21 reinforced concrete buildings which are mostly categorized as moment resisting frames has been selected for vulnerability study. A case study has been conducted on low rise with 6 (six) buildings and 15 numbers of medium rise building. The buildings are analyzed using Finite Element Modeling (FEM) under different types of analyses including Free Vibration Analysis (FVA), and Time History Analysis (THA) considering low to medium earthquake intensities. Different intensities of earthquake load, 0.01g up to 0.5g are applied to the structures to know the maximum allowable earthquake load intensities for the buildings. In the non-linear analysis of modal frames, it indicates that most of the buildings were categorised in the moderate damage level where there is no structural damage but some non-structural damage are expected. Most of the buildings were collapse with the intensity of 0.5g. The performances of the structure are shown by the yield point at beam-column connections where the internal forces at beam elements exceed the design capacity of the beams. The study indicates that the plastic hinge initially formed on the beam at the lower storey level for medium-rise of building frame. However for low rise building, it shows that the plastic hinge formed begun at low and higher storey level at beam.